Assessment of the "nearly normal" cervical spine radiograph: C2-C3 pseudosubluxation in an adult with whiplash injury. Issue 12 (18th November 2005) - Curtin, P; McElwain, J
Abstract : C2-C3 pseudosubluxation is a well recognized normal anatomical variant in children and this physiological spondylolisthesis often makes the interpretation of paediatric cervical spine radiographs difficult. In direct contrast, this finding is rare in adults and has not been reported as a diagnostic difficulty following neck injury. We report a case of C2-C3 pseudosubluxation occurring in a 27 year old woman presenting with neck pain 1 week after a road traffic accident. Although there are effective radiological guidelines for cervical spine radiograph evaluation in children, there is no evidence that these can be applied to the adult cervical spine. Flexion and extension cervical spine views have limitations. In such cases, magnetic resonance imaging is required to definitively exclude pathological injury.